Peran Gratitude Sebagai Mediator Antara Perceived Teacher’s Social Support dan Purpose in Life Pada Remaja - Aisah, Nurul; Yuliawati, Livia (Jurnal Psikologi Perseptual, 2024)
During adolescence, students begin to develop purpose in life and strategies to achieve them. The perceived social support of teachers is an initial stimulus for students to discover life goals. However, gratitude can also be a positive predictor for students to reflect on support, experiences, and challenges to find purpose in life that have an impact on the environment. The present study focused on examining the effect of perceived teachers' social support on purpose in life with gratitude as the mediator variable. This study used quantitative methods with a mediation design. The participants in this study were 204 SMA/MA/SMK students in grades 10-12, aged 15-18 years, and domiciled in Indonesia. Data collection used accidental sampling and snowball sampling where questionnaires were distributed online through social media. Data analysis was conducted using JASP 0.14.1 and hypothesis testing through mediation analysis with a causal steps model. The results of the mediation analysis showed that perceived teachers' social support has a significant influence on purpose in life through gratitude as a mediator variable, but the resulting mediation effect is partial. The implications of this research can help the school environment, especially teachers, in helping students find a meaningful purpose in life.Pada usia remaja, pelajar mulai merancang purpose in life dan strategi untuk mencapainya. Adanya perceived teacher’s social support menjadi stimulus awal bagi pelajar untuk menemukan purpose in life. Akan tetapi gratitude juga dapat menjadi prediktor positif bagi pelajar untuk merefleksikan dukungan, pengalaman, dan tantangan untuk menemukan purpose in life yang berdampak bagi lingkungan. Melalui penelitian ini, peneliti berfokus untuk menguji pengaruh perceived teacher’s social support terhadap purpose in life dengan gratitude sebagai variabel mediator. Penelitian ini menggunakan metode kuantitatif dengan desain mediasi. Partisipan dalam penelitian ini adalah pelajar SMA/MA/SMK kelas 10-12, berusia 15-18 tahun, dan berdomisili di Indonesia. Pengambilan data menggunakan accidental sampling dimana kuesioner disebarkan secara online melalui media sosial. Analisis data dilakukan menggunakan JASP 0.14.1 dan uji hipotesis melalui analisis mediasi dengan model causal steps. Hasil analisis mediasi menunjukkan perceived teacher’s social support memiliki pengaruh yang signifikan terhadap purpose in life melalui gratitude sebagai variabel mediator, tetapi efek mediasi yang dihasilkan bersifat parsial. Implikasi hasil penelitian ini dapat membantu lingkungan sekolah terutama guru dalam mendampingi siswa menemukan purpose in life yang bermakna.